Pengelolaan Cagar Budaya Sebagai Aset Pemerintah Daerah - Marta Lahang (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this study is to describe the management of Cultural Heritage as a Regional Government Asset through the Department of Education and Culture of Tana Tidung Regency and to determine the supporting factors and inhibiting factors in the management of cultural heritage as a Regional Government Asset. The type of research is qualitative. Sources of information are the Department of Education and Culture, Traditional Leaders, and Disparpora. Data collection techniques are interviews, observations, and documentation/Field Notes. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The results of the study revealed that the management of cultural heritage as a regional government asset includes four main stages: (1) Planning, which is based on regional regulations and policies; (2) Organization, in the form of coordination between related departments and institutions to maximize management functions; (3) Mobilization, by involving the active role of the government, community, and stakeholders; and (4) Supervision, to ensure that its implementation is in accordance with the objectives. The main supporting factors are government commitment through the placement of caretakers, HR training, and policy support. However, significant challenges are also encountered, such as regulations that are not yet strong, limited budget allocation, difficult geographic access, and limited infrastructure and quality HR. The conclusion of this study confirms that strengthening cultural heritage management requires multi-sector collaboration to develop more comprehensive regulations, increase budgets, improve infrastructure, and develop human resource capacity. This step not only supports preservation, but also optimizes cultural values ​​as sustainable assets for regional development. Keywords: Cultural Heritage, Management, Regional Government Assets.